Histological and molecular classification of gastrointestinal polyps - Haumaier, Franziska; Sterlacci, William; Vieth, Michael (Best Practice & Research in Clinical Gastroenterology, 2017)
Endoscopic diagnosis and treatment for gastrointestinal polyps became widely available within the last decades. Exact terminology is important for further therapeutic steps, follow up or treatment. Gastroenterologists, Oncologists, Surgeons and Pathologists need to be aware of the most recent terminology to ensure proper risk assessment and subsequent treatment if necessary. This manuscript aims to list the variety of gastrointestinal polyps and the molecular background where appropriate.
CRIS-Team Scopus Importer:2025-03-05
Keywords: Carcinoma; Colon; Gastrointestinal tract; Polyps; Small bowel; Stomach